(untitled) (Tazakka: Jurnal Pendidikan dan Keislaman, 2024)
The government has made efforts to support prospective teachers in developing their 21st-century competencies by launching the Kampus Mengajar program. However, teachers must also possess fundamental teaching skills, which are typically developed during microteaching sessions and have been integrated into the Kampus Mengajar program. Therefore, it is essential to evaluate the skills of prospective teachers participating in the program, particularly in areas such as set induction, closure, and classroom management.This research employs a qualitative method with a case study approach. Data were collected using observation, interviews, and documentation techniques. The observational assessment data are presented as percentages. The research results indicate that the skill level of prospective teachers in set induction and closure is 46.66%, categorized as adequate, while their classroom management skill level is 66.66%, categorized as good.